Development Of Learning Media Based On Wondershare Filmora Software On Integrated Thematic Learning Elementary School - M Aidhal Fikri; Yanti Fitria (ILIN Institute Makassar, 2022)
This study aims to determine the validity and practicality of learning media based Wondershare Filmora software in integrated thematic learning. This type of research is R&D (Research and Development). This means that research is responsible for the results of new products or improvements to existing products. This study uses a 4-D development model. Consists of define, design, development, and disseminate. The subjects of the pilot study were 3 experts, 1 class teacher and 30 third grade elementary school students. The instruments used were expert validation sheets, teacher and student response questionnaires. The results showed: (1) Wondershare Filmora software in integrated thematic learning theme 6 Energy and its Changes in Elementary School was declared very valid with an average score of 94,12% media experts, material experts 90.67% and linguists 97.50%, (2) Teacher and student responses to software -based learning media trials Wondershare Filmora in Elementary School obtained a very practical category with an average value of 92.50% teacher responses and 95.83% student responses.